Surgical Anatomy and Exercises Using the Chicken Thigh Sciatic Nerve for Microsurgery Training - Chong, Alphonsus K.S.; Le, Lan Anh T.; Lahiri, Amitabha; Yusoff, Khadijah; Yip, George W.; Pan, Feng; Teo, Wendy; Liao, Janice C.Y.; Lim, Jin Xi (Journal of Hand and Microsurgery, 2022)
Introduction Vessel repair in a chicken thigh is commonly used in microsurgery training model. The sciatic nerve is closely associated with the vessels and has been used for training nerve coaptation, which has different technical considerations from vessel anastomosis. We describe in detail the relevant surgical anatomy and training exercises that can be used with this model.Methods With 32 fresh store-bought chicken thighs, 16 were used to analyze the gross and histological features of the sciatic nerve, and 16 were intended to create and perform training models.Results The average visible length of the nerve in the thigh was 51 mm (standard deviation [SD] 2.57 mm). The average diameter of the nerve was 2 mm (SD 0.33 mm) and was largest at its proximal end (3.21 mm, SD 0.27 mm). The nerve consistently branched into two along the chicken thigh, with more branching subsequently. This simulation model is appropriate not only for the classical end-to-end epineural suture, but also for advanced exercises, in terms of longitudinal fasciculus dissection, mismatched size nerve transfer, injured nerve preparation, and vein conduit technique. Dyeing of nerve fascicles enhanced the visibility of nerve surface quality.Conclusion The sciatic nerve in the chicken thigh is a suitable and accessible model for microsurgery training. The branching and fascicular patterns of the nerve lends itself well to both novice training and advanced simulation. We have incorporated this model into our training curricula.
Keywords: microsurgery training; nerve repair; nerve coaptation